2022
DOI: 10.1590/fst.71622
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tartary buckwheat bran flour modified by heat-moisture treatment in steamed bread processing

Abstract: The rheological properties of dough from modified Tartary buckwheat bran flour (MTBF) by heat-moisture treatment (HMT) and wheat flour (WF) were investigated in this study, and the application of MTBF in steamed bread processing was also evaluated. The results showed that the addition of MTBF had a significant effect on torque curve and parameters of the dough. With the increase of the weight proportion of MTBF in the blend (W MTBF ), the water absorption of the dough gradually increased, the protein weakening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Research on the impact of heat-moisture treatment on the characteristics of Tartary buckwheat flour and starch has been performed to date [ 82 , 83 ]. More recently, Zhang et al [ 84 ] applied Tartary buckwheat bran modified by heat-moisture treatment in steam bread making. They concluded that the steamed bread had similar qualities compared to the control wheat steam bread when the weight proportion of Tartary buckwheat bran was less than 20%.…”
Section: Food Uses Of Tartary Buckwheat Branmentioning
confidence: 99%
“…Research on the impact of heat-moisture treatment on the characteristics of Tartary buckwheat flour and starch has been performed to date [ 82 , 83 ]. More recently, Zhang et al [ 84 ] applied Tartary buckwheat bran modified by heat-moisture treatment in steam bread making. They concluded that the steamed bread had similar qualities compared to the control wheat steam bread when the weight proportion of Tartary buckwheat bran was less than 20%.…”
Section: Food Uses Of Tartary Buckwheat Branmentioning
confidence: 99%
“…For instance, the addition of buckwheat hull decreased pasting properties of starch due to the water holding capacity of dietary fibre (Liu et al, 2022). The addition of buckwheat bran flour caused an increase in water absorption of steamed bread dough due to the high fibre and lipid content of buckwheat (Zhang et al, 2022). Alfaris et al (2022) illustrated that dough formulated with wheat bran had a higher value of dough stability in comparison to dough with wheat flour only due to dilution of gluten and disruption of the gluten network structure.…”
Section: Introductionmentioning
confidence: 99%